The Ngaha Aina Ngoho Philosophy as the Basis for the Ecological Movement Based on the Local Wisdom of the Mbojo Community - Ahlan (Jurnal Sosial dan Humaniora, 2026)
The philosophy of Ngaha Aina Ngoho is the local wisdom of the Mbojo people, which contains ethical values regarding the balance of human relations with nature, particularly in the context of responsible resource use. This philosophy literally affirms the principle of "eat but do not consume," which reflects moderation, sustainability, and rejection of excessive exploitation. This article aims to analyse Ngaha Aina Ngoho as a normative and practical basis for local wisdom-based ecological movements amid the contemporary environmental crisis. This study uses a qualitative approach with library research, examining written sources such as books, journal articles, previous research results, and cultural documents and local wisdom of the Mbojo community relevant to ecological issues. Data analysis was conducted descriptively and analytically, emphasising critical interpretation of the values, meanings, and socio-ecological functions of the Ngaha Aina Ngoho philosophy. The results of the study show that Ngaha Aina Ngoho not only functions as a symbolic-cultural value but also represents an ecological ethic that emphasises the principles of moderation, intergenerational responsibility, and environmental sustainability. This philosophy has great potential as an ethical framework for building ecological awareness in communities based on local cultural identity. However, the challenges of modernisation, economic pressures, and shifting cultural values have implications for the weakening of the internalisation of this philosophy in social practice. This study affirms that the revitalisation of Ngaha Aina Ngoho as the basis for local ecological movements has strategic relevance in formulating a contextual, participatory model of environmental conservation rooted in local wisdom as a civilised response to the global environmental crisis.